Efek Konsentrasi Pupuk Organik Cair dan Jarak Tanam Terhadap Karakter Agronomi dan Serapan N Pada Tanaman Selada Hijau (Lactuca sativa L.) - Sri Endang Agustine; Lia Amalia; Tien Turmuktini (Publikasi Indonesia, 2022)
This study intends to study the interaction of Liquid Organic Fertilizer concentration and plant spacing on agronomic characters and N uptake in lettuce. It was carried out in the experimental area of ??Chemical Agro Lembang, West Bandung Regency and carried out from September 2021 to October 2021 with an altitude of 1250 m above sea level. The experimental method used was a factorial randomized block design (RAK). The first factor was the POC concentration consisting of 3 levels, namely 0, 2 and 4 ml L-1 and the second factor was the spacing between 3 levels, namely 30 cm x 25 cm, 25 cm x 25 cm and 20 cm x 25 cm. The results of the study showed that there was no interaction between POC concentration and plant spacing in observations. Giving a concentration of 4 ml L-1 POC and plant spacing with treatment of 30 cm x 25 cm gave the highest yield on agronomic characters and N uptake in lettuce. The optimum POC concentration for each plant spacing in the treatment (P1) which was 0.774 tons h-1 was able to increase the maximum yield of fresh plant weight by 95.93 g per plant, the concentration (P2) which was 2.145 tons h-1 was able to increase the maximum yield of plant weight. fresh weight per plant as much as 162.18 g per plant and the optimum concentration for (P3) which is 2.48 tons ha-1 can increase the maximum yield of fresh weight per plant as much as 131.30 g per plant.